Upper Limits to the Proper Motions of JuMBO 24, a Jupiter-mass Binary Object Candidate in Orion - Luis F. Rodríguez; Laurent Loinard; Luis A. Zapata; Gisela N. Ortiz-León (The Astrophysical Journal)
Using JWST near-infrared data of the inner Orion Nebula, S. G. Pearson & M. J. McCaughrean detected 40 binary systems they proposed to be Jupiter-mass binary objects (JuMBOs)—although their actual nature is still in debate. Only one of the objects, JuMBO 24, was detected in the radio continuum. Here, we report on new radio continuum (10 GHz) Karl G. Jansky Very Large Array (VLA) detections of the radio counterpart to JuMBO 24, and on an unsuccessful search for 5 GHz continuum emission with the High Sensitivity Array (HSA). From our new VLA detections and adopting a distance to the region, we set an upper limit of ≃6 km s ^−1 to the velocity of the radio source in the plane of the sky. This upper limit favors an origin for this source similar to that of stars, that is, from a stationary contracting core. The nature of the radio emission remains uncertain, but the lack of strong variability (all VLA observations are consistent with a steady flux of ∼50 μ Jy), of detection on long HSA baselines, and of detectable circular polarization in VLA data do not favor a nonthermal origin.